Companies to promote CSR impact on employees: High‐performance work systems as a moderator. Issue 4 (30th July 2022) - Liang‐Chih, Huang; Tzeng‐Tian, Huang; Chien‐Bin, Hsu
Abstract: Corporate social responsibility (CSR) has been of much public concern in recent years. This study uses the Conservation of Resources Theory to discuss the measures that organizations can take to ensure that resources are not lost when they face institutional pressures. We distributed questionnaires to Taiwanese small‐ and medium‐sized enterprises (SMEs) in two phases. The results reveal the following measures pertinent to enterprise management bodies: (1) SMEs faced with external institutional pressure must promote CSR strategies to secure existing organizational resources; (2) spreading awareness on and taking actions for CSR promotion by SMEs, in response to changes in the external institutional environment, can improve corporate image and increase employees' intention to stay; and (3) measures concerning high‐performance work systems can help unleash the full potential of human resource management and facilitate enterprises to introduce CSR. Some important theoretical implications emerge in this study. Based on the Conservation of Resources Theory, we argue that the stressor faced by SMEs is not a threat, but a factor that creates or preserves organizational resources. Through the application of this theory, we enrich the CSR model. Further, the feasibility of high‐performance work systems, as a moderator of institutional pressure, is determined.